2023
DOI: 10.3389/fnut.2023.1138488
|View full text |Cite
|
Sign up to set email alerts
|

The association between oxidative balance score and periodontitis in adults: a population-based study

Abstract: IntroductionThe pathogenesis between oxidative stress and periodontitis was correlated. The Oxidative Balance Score (OBS) is a systematic tool to assess the effects of diet and lifestyle in relation to oxidative stress. However, the association between OBS and periodontitis has not been reported previously.MethodsSixteen dietary factors and four lifestyle factors were selected to score the OBS. Multivariate logistic regression and sensitivity analysis were used to investigate the relationship between OBS and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…Liu et al [44] found that TOBS and DOBS levels were positively correlated with vascular endothelial function, revealing another link between OBS and cardiovascular disease. Qu et al [45] illustrated a negative linear association between OBS and periodontitis among US adults, and the risk of periodontitis was reduced by 11% for every 1 unit increase in OBS, proposing OBS as a viable biomarker for periodontitis evaluation. The accruing body of evidence underscores the potential of OBS in evaluating a gamut of diseases, laying a robust foundation for our trailblazing study aimed at elucidating the relationship between OBS and RA.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [44] found that TOBS and DOBS levels were positively correlated with vascular endothelial function, revealing another link between OBS and cardiovascular disease. Qu et al [45] illustrated a negative linear association between OBS and periodontitis among US adults, and the risk of periodontitis was reduced by 11% for every 1 unit increase in OBS, proposing OBS as a viable biomarker for periodontitis evaluation. The accruing body of evidence underscores the potential of OBS in evaluating a gamut of diseases, laying a robust foundation for our trailblazing study aimed at elucidating the relationship between OBS and RA.…”
Section: Discussionmentioning
confidence: 99%
“…The OBS is a tool used to assess overall redox homeostasis in individuals and has been shown to be associated with colorectal cancer, CVD, and chronic kidney disease in previous epidemiological studies ( 33 ). More recent studies using NHANES have suggested that higher OBS is associated with improved cognitive function and depressive symptoms, and reduced risk of periodontitis and diabetes compared with those with the lowest OBS ( 7 , 8 , 34 , 35 ). After adjustment for all included confounders, OBS treated as both a continuous and a categorical variable, was associated with the risk of NAFLD but not AHF.…”
Section: Discussionmentioning
confidence: 99%
“…A broad range of covariates was carefully evaluated, guided by existing literature [ [16] , [17] , [18] , [19] , [20] ]. These included demographic variables such as age, race/ethnicity, gender, educational attainment, marital status, poverty-to-income ratio (PIR), and total energy intake (kcal) [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Generally, a higher OBS indicates a dominance of antioxidants over pro-oxidants. Numerous studies have established a negative correlation between OBS and the prevalence of various diseases, such as leukocyte telomere length [ 15 ], diabetes mellitus [ 14 ], osteoarthritis [ 16 ], and periodontitis [ 17 ]. However, research exploring the potential link between OBS and migraine is notably limited.…”
Section: Introductionmentioning
confidence: 99%